The relationship of psychological capital, transformational leadership, and internal communication to work engagement in organizations - Astri, Dyah Retnaning; Purba, Debora Eflina (International journal of health sciences, 2024)
Organization A, which represents the country in the oil and gas industry and is tasked with managing oil and gas activities in Indonesia to ensure national energy security, requires employees with high work engagement. This requires enthusiasm, dedication, and perseverance to contribute fully to their work. However, human resource management surveys and several phenomena analyzed show that work engagement in Organization A is low. This research consists of two studies: a research study and an intervention study. This research aims to analyze the relationship between psychological capital (individual internal factors), transformational leadership (individual external factors), and internal communication (organizational factors) on work engagement using a sample of 267 employees of Organization A. Using a quantitative design supported by qualitative data, and found that individual psychological capital, transformational leadership style, and internal communication in the organization significantly predicted work engagement. Among these factors, internal communication predicted work engagement beyond psychological capital and transformational leadership. An intervention study involving 23 participants was designed to determine the effectiveness of an internal communication strategy training program in increasing work engagement. Results from the intervention study showed significant improvements in participants' pre-test and post-test scores, indicating the effectiveness of the program in increasing work engagement.